2016
DOI: 10.1007/s10029-016-1516-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and hernia development 5 years after open abdomen treatment with vacuum-assisted wound closure and mesh-mediated fascial traction

Abstract: VAWCM treatment results in high incidence of IH. However, at five years, there was no detectable difference in abdominal wall complaints and QoL in patients with IH compared to those without. Lower QoL appeared mainly to be associated with the presence of major co-morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 28 publications
2
33
0
1
Order By: Relevance
“…The incisional hernia rate ranged from 21% at 21 months follow up to 54% at 63 months of follow up. The incisional hernia repair rate was 42% [15] and 33% [14] in the two large prospective studies, respectively. The study patients reported lower short form health survey (SF-36) scores than the mean reference population, mainly dependent on the prevalence of major co-morbidity [14].…”
Section: Study Characteristics Of Long-term Outcome Studiesmentioning
confidence: 92%
See 4 more Smart Citations
“…The incisional hernia rate ranged from 21% at 21 months follow up to 54% at 63 months of follow up. The incisional hernia repair rate was 42% [15] and 33% [14] in the two large prospective studies, respectively. The study patients reported lower short form health survey (SF-36) scores than the mean reference population, mainly dependent on the prevalence of major co-morbidity [14].…”
Section: Study Characteristics Of Long-term Outcome Studiesmentioning
confidence: 92%
“…The incisional hernia repair rate was 42% [15] and 33% [14] in the two large prospective studies, respectively. The study patients reported lower short form health survey (SF-36) scores than the mean reference population, mainly dependent on the prevalence of major co-morbidity [14]. Quality of life measured with the SF-36 questionnaire and abdominal wall specific complaints measured with a modified ventral hernia pain questionnaire (VHPQ) (Fig.…”
Section: Study Characteristics Of Long-term Outcome Studiesmentioning
confidence: 92%
See 3 more Smart Citations